2013
DOI: 10.1016/j.biomaterials.2013.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

Bladder tissue regeneration using acellular bi-layer silk scaffolds in a large animal model of augmentation cystoplasty

Abstract: A cellular scaffolds derived from Bombyx mori silk fibroin were investigated for their ability to support functional tissue regeneration in a porcine model of augmentation cystoplasty. Two bi-layer matrix configurations were fabricated by solvent-casting/salt leaching either alone (Group 1) or in combination with silk film casting (Group 2) to yield porous foams buttressed by heterogeneous surface pore occlusions or homogenous silk films, respectively. Bladder augmentation was performed with each scaffold grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 32 publications
1
67
2
Order By: Relevance
“…CK7, CK18, and CK19 are the markers expressed throughout all layers in normal urothelium [7] . Available literature towards urothelium basal layer characterization have shown that urothelium cells were expressing phenotypic marker CK5 and CK17, but they did not express phenotypic marker CK20, which is generally associated with differentiated superficial cells [7,8,9] . The urothelium or transitional epithelium of the urinary tract shows alterations in the expression and configuration of cytokeratin isotypes associated with stratification and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CK7, CK18, and CK19 are the markers expressed throughout all layers in normal urothelium [7] . Available literature towards urothelium basal layer characterization have shown that urothelium cells were expressing phenotypic marker CK5 and CK17, but they did not express phenotypic marker CK20, which is generally associated with differentiated superficial cells [7,8,9] . The urothelium or transitional epithelium of the urinary tract shows alterations in the expression and configuration of cytokeratin isotypes associated with stratification and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial stem cells capable of regenerative potential were isolated from mice tissue, which was found to express sonic hedgehog and p63 proteins in the basal cell layers of the bladder urothelium [7,8] . A recent report has also shown p63 expression in porcine urothelial and human urothelial cells [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Though out of the true synthetic biomaterials field,"silk fibroin"made scaffolds, coated with ECM proteins, have been timely used, in animal model bladder tissue engineering, as templates for urothelial/smooth muscle cell seeding procedure, thus achieving a construct endowed with effective structural and functional proper such as particularly biodegradability, plasticity, compliance (42,43). In this regard, recent animal model studies have shown that the stretched electrospun silk fibroin matrix implantation can strongly promote bladder tissue regeneration with proper structure/function features, in comparison with BAM (44).…”
Section: Regenerative Medicine and Tissue Engineering Research Develomentioning
confidence: 99%
“…To overcome the limitation, combined scaffolds have been developed. Combination fabrication is a method that fabricates scaffolds with two or more fabrication techniques, such as porous scaffold/ particles, 24 porous scaffold/membrane, 45 and hydrogel/ fibers. 46 Combination fabrication can better match the tissue regeneration requirement and broaden the use of SF materials.…”
Section: Combined Scaffoldsmentioning
confidence: 99%